Examining the English Learner Policy Ecology: How Educators Navigated the Provision of Designated English Language Development (ELD) Support at the Secondary Level. Issue 1 (1st January 2022) - Hopkins, Megan; Weddle, Hayley; Lavadenz, Magaly; Murillo, Marco A.; Vahdani, Tara
ABSTRACT: Under federal civil rights law, U.S. school districts have a dual obligation to provide students identified as English learners (ELs) with designated English-language development (ELD) instruction and integrated ELD support during core content instruction. Drawing on an analysis of interviews with 96 educators in two large California districts, we use an ecological approach to explore how district and school staff navigated the provision of designated ELD at the secondary level. Findings revealed that state and school structures shaped district culture in ways that deemphasized designated ELD for ELs across proficiency levels. Rather than emphasizing integrated ELD approaches that foster language development through content, however, these structural and cultural dynamics meant that many ELs received few, if any, linguistic supports. Although federal oversight and leaders' agency helped to shift this trend and support ELs' access to ELD, the primary mode of delivery was through required ELD courses, which research shows can preclude ELs' access to core content. These findings have important implications for policymakers and leaders seeking to ensure that all ELs have equitable access to language and content instruction.